RESILIENCE OF EVENT INDUSTRY IN BALI POST COVID-19 - Ni Luh Putu Intan Nirmalasari; Ni Made Rinayanthi (Journal of Innovation Research and Knowledge, 2024)
The event industri makes a big contribution to Bali's economy and is able to provide many jobs for the community. However, reflecting on the pandemic situation, the Covid-19 industri needs to adapt to be more resilient to external risks. Various changes in the industri occurred during the pandemic recovery era, including the implementation of health protocols, broadcasting of domestic tourist visits, travel preferences for groups with flexible numbers and changes in consumer behavior. These changes must of course be balanced with adaptations in the tourism industri to change fundamental systems in business practices. Organizational resilience is needed in industrial events so that it can face changes due to the pandemic. Organizational resilience depends on the ability to use the knowledge and resources contained in internal and external networks and relationships. Research was conducted on the events industri in Bali to examine efforts to prepare organizational resilience in facing crises. The method used in this research is descriptive qualitative